2022
DOI: 10.3390/ijerph19053130
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects on Emotional Stress and Sleep Quality of Forest Healing Program for Exhausted Medical Workers during the COVID-19 Outbreak

Abstract: This study targeted medical workers, who are currently being subjected to an excessive workload and emotional stress during the COVID-19 outbreak. Various treatment programs, such as a relaxation program to relieve stress, a walk in the forest, and woodworking were provided to the participants as forest healing therapies. We enrolled 13 medical workers (11 females, 2 males). Before and after forest healing therapy, stress and sleep-related questionnaires and levels of salivary cortisol, dehydroepiandrosterone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…Private green spaces contributed more to the reduction of anxiety and fear than the public green spaces. Kim, Choi, and Kim (2022) , Korea Medical workers (13, 42.23 ± 10.99 years, 85%, n.a.) November 2021 Experimental, longitudinal, quantitative, survey + physiological parameter assessment Investigate effects of a forest healing program on health during COVID-19 Forest healing therapy Two-day forest treatment program with various components, e.g., a walk in the forest, woodworking, and relaxation program Stress Sleep quality Perceived stress scale (PSS) Epworth sleepiness scale (ESS) Stanford sleepiness scale (SSS) Pittsburgh Sleep Questionnaire Index (PSQI) Hospital Anxiety and Depression scale (HADS) Somatization symptoms (KSCL95) Salivary cortisol Dehydroepiandrosterone sulfate (DHEA-S) Melatonin There was an improvement in sleep duration from prior to post-treatment (+41.54 ± 46.70 minutes, p < 0.05) as well as in perceived stress (−2.69 ± 3.73, p < 0.05) and in dehydroepiandrosterone sulfate (−1.42 ± 2.07, p < 0.05), indicating that some sleep and stress parameters improved.…”
Section: A1 Detailed Search Strategy Implementedmentioning
confidence: 99%
“…Private green spaces contributed more to the reduction of anxiety and fear than the public green spaces. Kim, Choi, and Kim (2022) , Korea Medical workers (13, 42.23 ± 10.99 years, 85%, n.a.) November 2021 Experimental, longitudinal, quantitative, survey + physiological parameter assessment Investigate effects of a forest healing program on health during COVID-19 Forest healing therapy Two-day forest treatment program with various components, e.g., a walk in the forest, woodworking, and relaxation program Stress Sleep quality Perceived stress scale (PSS) Epworth sleepiness scale (ESS) Stanford sleepiness scale (SSS) Pittsburgh Sleep Questionnaire Index (PSQI) Hospital Anxiety and Depression scale (HADS) Somatization symptoms (KSCL95) Salivary cortisol Dehydroepiandrosterone sulfate (DHEA-S) Melatonin There was an improvement in sleep duration from prior to post-treatment (+41.54 ± 46.70 minutes, p < 0.05) as well as in perceived stress (−2.69 ± 3.73, p < 0.05) and in dehydroepiandrosterone sulfate (−1.42 ± 2.07, p < 0.05), indicating that some sleep and stress parameters improved.…”
Section: A1 Detailed Search Strategy Implementedmentioning
confidence: 99%
“…Forest healing merupakan bentuk pemanfaatan hutan sebagai media untuk penyembuhan yang terkait dengan aspek fisiologis maupun mental. Istilah yang berkembang juga sangat bervariasi diantaranya forest bathing (mandi hutan), forest walking (berjalan di hutan), forest therapy (terapi hutan), serta sedikit yang menggunakan istilah nature therapy (terapi alam) (Kim et al, 2022;Satyawan et al, 2022).…”
Section: Pendahuluanunclassified
“…Aktivitas dilakukan melalui pengaturan napas dan pemfokusan pikiran dengan cara menenangkan diri dan berdiam di suatu tempat. Meditasi pernapasan dan pikiran terbukti dapat meningkatkan daya tahan, mengatasi stres dan depresi, serta meningkatkan kualitas hidup (Han & Koo, 2018), mengurangi stress (Kim & Choi, 2021), serta mengurangi emosional dan peningkatan kualitas tidur (Kim et al, 2022). Kegiatan berendam dilakukan dengan memasukan tubuh ke dalam badan air sungai.…”
Section: Demografi Respondenunclassified
“…My research team found that Shinrin-yoku significantly increase serum dehydroepiandrosterone sulfate (DHEA-S) levels [ 29 ]. On the other hand, Kim et al [ 54 ] reported that a Forest Healing Program in a Korean forest reduced DHEA-S levels. Therefore, the effect of forest bathing on DHEA-S needs further research.…”
Section: Evidence-based Forest Medicinementioning
confidence: 99%
“…In fact, my research team has found that virtual exposure to forest environments based on audio-visual stimuli brought by a short computer video showing forest environments, with an urban video as a control showed effective to reduce negative emotions such as anxiety in people forced by lockdown in limited spaces in Italy during COVID-19 pandemic [ 62 ]. Kim et al also reported the positive effects of a Forest Healing Program in a Korean forest on motional stress and sleep quality for exhausted medical workers during the COVID-19 Outbreak in Korea [ 54 ]. Therefore, Shinrin-yoku may have preventive effect on COVID-19-induced mental stress and mental disorders.…”
Section: Evidence-based Forest Medicinementioning
confidence: 99%